Cimatario National Park in Queretaro, Mexico: Towards Sustainable Tourism - HUERTA-MENDOZA, Ana-Karen; FISCHER, Laura (Journal of Environmental Management and Tourism; Vol 13 No 3 (2022): JEMT, Volume XIII, Issue 3(59), Summer 2022, 2022)
El Cimatario National Park in Querétaro is an ecological reserve located in the City of Querétaro, Mexico, which has excellent attributes to develop sustainable tourism and in turn, conserve the biodiversity of the area. The article aims to know the strengths, weaknesses, threats and opportunities that the Cimatario Park currently presents and with the results obtained propose a marketing plan with a sustainable approach, which allows this ecological reserve to maintain the contact of man with the environment that surrounds him but counting on rules and procedures to maintain the present and future environment.